Rpr- and hid-driven cell death in Drosophila photoreceptors. - Hsu, C.D.; Adams, S.M.; O'Tousa, J.E. (Vision Research, 2002)
The reaper (rpr) and head involution defective (hid) genes mediate programmed cell death (PCD) during Drosophila development. We show that expression of either rpr or hid under control of a rhodopsin promoter induces rapid cell death of adult photoreceptor cells. Ultrastructural analysis revealed that the dying photoreceptor cells share morphological features with other cells undergoing PCD. The anti-apoptotic baculoviral P35 protein acts downstream of hid activity to suppress the photoreceptor cell death driven by rpr and hid. These results establish that the Drosophila photoreceptors are sensitive to the rpr- and hid-driven cell death pathways.